(untitled) (Palimpsesto, 2026)
Six years after the social uprising in Chile and in dialogue with the systematization of the Brazilian collective project OCUPAS, this article systematizes memories and learnings about the transformations of the social and what we define as the cultivation of practices of dignity in the face of neoliberal devastation. Drawing from the Chilean context, where the neoliberal university and the “necrophagous market of the social” prioritize logics of competition, precarization, and structural oblivion, rendering invisible the knowledge emerging from territorial and community practices, the text proposes the exercise of remembering as an ethical imperative in order not to succumb to horror and dispossession. Through “(con)fabulations” — narratives and everyday complicities that reinvigorate collective memory — communities can resist violence and isolation. The 2019 uprising is analyzed not as an event with a concrete end, but as the manifestation of a transgenerational desire to live with dignity, connected to previous struggles for life and territory. Finally, the article reflects on how grassroots territorial organizations, including those engaged in the implementation of social projects, sustain common life through gestures of care, tenderness, and companionship, reinventing forms of encounter despite the landscape of exhaustion and precarization of earlier forms of militancy and activism. It concludes by stressing the need to strengthen micro-histories and experiential learnings as a way of revitalizing political imagination and sustaining the desire for revolt.